Low-Carbon Energy Technologies: Potentials of Solar and Nuclear Energy Sources for Sustainable Economic Development in Bangladesh - Mohammad Rashedul Hoque; Saad Hasan; Nidhu Lal Banik; Nisar Ahmed; Shafkat Reza Chowdhury (International Journal of Technology for Business (IJTB), 2019)
Electricity shortage has become a major challenge to continued economic growth in Bangladesh. The country is growing in terms of GDP growth at a rate of 7% a year. Bangladesh is expected to move towards 23rd position globally by 2050 from its position 31 in 2014, in terms of GDP at purchasing power parity (PPP). The demand for electricity is forecasted to be 61,164 MW within the same period. Currently, electricity generation in Bangladesh is highly dependent on fossil fuels, nearly 59% is produced from natural gas followed by furnace oil, diesel and coal, while only 3% from renewables. Electricity generation is the largest single source of GHG (greenhouse gas) emissions in Bangladesh, and thus finding alternative energy source has become imperative for the country. Solar and nuclear energy sources have the potentials to be utilized for low-carbon energy sector and thus for a sustainable economic development in Bangladesh. Barriers to solar and nuclear energy will be reduced significantly in coming years with technological advancement. However, energy policies need to be revised to facilitate low-carbon energy technologies. Besides, more international collaboration is highly required not only to import new technologies but also to enhance the capacity of research and development (R&D) as well as overall adoption of the technologies.
Keywords: 650; Economic Growth; Electricity Shortage; Fossil Fuel; Greenhouse Gas; Low-carbon Energy; Renewable Energy; Nuclear Energy; Bangladesh